WEST ANATOLIAN MINING IN EARLY BRONZE AGE (3000-2000 BC) - Harun Oy (Journal of Ancient History and Archaeology)
The discovery of people's mines and the use of them has been a major breakthrough in the development of civilization. In Anatolia, which has rich ore deposits, it is seen that people recognized the mines from the Neolithic Age. When the Early Bronze Age came, mining activities became very widespread. In western Anatolia, centers such as Troia, Limantepe and Beycesultan have become masters of metal production. In this article, in the Early Bronze Age, the mining of the western Anatolian region is evaluated. In this context, mineral deposits of the Western Anatolian region, mineral products and their usage areas, archaeological sites that found metal were investigated. In addition, the use of metals such as copper, tin, bronze, lead, gold, silver and iron in the region has been discussed.